Bayesian Equilibrium and Incentive-Compatibility: An Introduction - Roger B. Myerson (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1983)
This paper is an introduction to the analysis of games with incomplete information, using a Bayesian model. the logical foundations of the Bayesian model are discussed. To describe rational behavior of players in a Bayesian game, two basic solution concerts are present: Bayesian equilibrium, for games in which the players cannot communicate; and Bayesian incentive-compatibility, for games in which the players can communicate. The concept of virtual utility is developed as a tool for characterizing efficient incentive-compatible coordination mechanisms.
Keywords: 330